Frequency of conjugative transfer of plasmid-encoded ISEcp1 - blaCTX-M-15 and aac(6')-lb-cr genes in Enterobacteriaceae at a tertiary care center in Lebanon - role of transferases - Araj George F; Corkill John E; Khairallah Marie-Therese; Harajly Mohamad; Matar Ghassan M (BMC, 2010)
Abstract Background The frequency of transfer of genes encoding resistance to antimicrobial agents was determined by conjugation in ESBL-producing and/or fluoroquinolone or aminoglycoside resistant Enterobacteriaceae clinical isolates at a tertiary care center in Lebanon. In addition, the role of tra genes encoding transferases in mediating conjugation was assessed. Methods Conjugation experiments were done on 53 ESBL-producing and/or fluoroquinolone resistant E. coli and K. pneumoniae and ESBL-producing S. sonnei isolates. Antimicrobial susceptibility testing on parent and transconjugant isolates, and PCR amplifications on plasmid extracts of the resistance-encoding genes: blaCTX-M-15 with the ISEcp1 insertion sequence, the aac(6')-lb-cr and qnrS genes, as well as tra encoding transferases genes were done. Random amplified polymorphic DNA (RAPD) analysis was performed to demonstrate whether conjugative isolates are clonal and whether they are linked epidemiologically to a particular source. Results Antimicrobial susceptibility testing on transconjugants revealed that 26 out of 53 (49%) ESBL-producing Enterobacteriaceae were able to transfer antimicrobial resistance to the recipients. Transfer of high-level resistance to the transconjugants encoded by the blaCTX-M-15 gene downstream the ISEcp1 insertion sequence against 3rd generation cephalosporins, and of low-level resistance against ciprofloxacin, and variable levels of resistance against aminoglycosides encoded by aac(6')-lb-cr gene, were observed in transconjugants. tra encoding transferase genes were detected exclusively in conjugative isolates. Conclusion In conclusion, the frequency of transfer of antimicrobial resistance in non clonal Enterobacteriaceae at the tertiary care center by conjugation was 49%. Conjugation occurred in isolates expressing the tra encoding transferase genes. Multiple conjugative strains harboring the plasmid encoded antimicrobial resistant genes were circulating in the medical center. Molecular epidemiology analysis showed that conjugative isolates are neither clonal nor linked to a particular site and transfer of antimicrobial resistance is by horizontal transfer of plasmids.